Evaluation of the Efficiency of the Universal Supply System of Gas Cylinder Vehicles. - Ilhom Iskandarovich Umirov; Shukurov Shokhzod Aslam o’g’li (Zien Journals, 2023)
This article analyzes the gas supply system cars with gas cylinders, its principle of operation and the types of gas equipment installed in cars
Keywords: car; engine; supply system